Understanding the role of shaft stiffness in the golf swing - MacKenzie, S. J.; Sprigings, E. J. (Sports Engineering, 2009)
The purpose of this thesis was to determine how shaft stiffness affects clubhead speed and how it alters clubhead orientation at impact. For the first time, a 3D, six-segment forward dynamics model of a golfer and club was developed and optimized to answer these questions. A range of shaft stiffness levels from flexible to stiff were evaluated at three levels of swing speed (38, 45 and 53 m/s). At any level of swing speed, the difference in clubhead speed did not exceed 0.1 m/s across levels of shaft stiffness. Therefore, it was concluded that customizing the stiffness of a golf club shaft to perfectly suit a particular swing will not increase clubhead speed sufficiently to have any meaningful effect on performance. The magnitude of lead deflection at impact increased as shaft stiffness decreased. The magnitude of lead deflection at impact also increased as swing speed increased. For an optimized swing that generated a clubhead speed of 45 m/s, with a shaft of regular stiffness, lead deflection of the shaft at impact was 6.25 cm. The same simulation resulted in a toe-down shaft deflection of 2.27 cm at impact. Using the model, it was estimated that for each centimeter of lead deflection of the shaft, dynamic loft increased by approximately 0.8°. Toe-down shaft deflection had relatively no influence on dynamic loft. For every centimeter increase in lead deflection of the shaft, dynamic closing of the clubface increased by approximately 0.7°. For every centimeter increase in toe-down shaft deflection, dynamic closing of the clubface decreased by approximately 0.5°. The results from this thesis indicate that improvements in driving distance brought about by altering shaft stiffness are the result of altered clubhead orientation at impact and not increased clubhead speed.